The Delft town fire of 1536 and the spread of arched fronts (Bulletin KNOB, 2007)
Among the many large town fires in the 16th century the fire of Delft in 1536 was the most extensive. The extent of this disaster is to be compared to a large bombing during the last World War. A lot of the rebuilt houses still exist, some even with the old facades. Four drawings from around 1785 of disappeared facades complete the picture and gave rise to this article (ill. 4. 10-12).After the fire the walls of churches and monasteries largely survived and the wooden roofs and vaults could be restored. The houses needed total renewal. There is not much evidence of guidance in this matter by the town council. Building regulations were temporarily suspended, but the use of joint walls was promoted, which saved brick and made the houses more spacious.After the disaster the Delft building trade had plenty of work clearing the rubble and carrying out emergency restorations for several years. Rich people were able to employ a building contractor from outside the town. This led to new types of facades with freer compositions. All known contacts were made through Dordrecht, which as the major commercial town maintained the relations with the Southern Netherlands. A lot of sculpture on the Delft facades also appears to be of Dordrecht origin.The new styles must have been imported along this route. (ill. 2, 3. 4. 5). In the retinue of this vanguard forms of facades were built that suited the various groups of commissioners (ill. 4-9). In cooperation with Dordrecht contractors new variations of facades were realised, applied by the latter in the entire working space of the southern Netherlands. Due to the division of the northern and southern Netherlands after 1600 Dordrecht lost its prominent position to Amsterdam. Delft reverted to a simple country town again. Just as Dordrecht it was one of the few Dutch towns that did not expand during the 17th century. The aftermath of the important Delft-Dordrecht period in the 16th century left its traces throughout the southwest Netherlands (ill. 11-12). Without an insight into the far-reaching consequences of a town fire it is impossible to understand why these prestige objects are found here.